Implementation of Culturally Responsive Teaching Approach of Sikambang Arts Through Plane Shapes Learning in Grade V of Elementary School - Sinaga, Syafira Amalia; Sukmawarti, Sukmawarti; Hidayat, Hidayat (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
This study is a qualitative descriptive study conducted at SDN 153007 Sorkam, Tapanuli Tengah Regency, with the aim of describing the effectiveness of electricity use in teaching and learning activities and the application of the Culturally Responsive Teaching approach to flat geometry material using Sikambang Art in grade V. Data were collected through observation and interviews, which were then analyzed to obtain an overview of the learning conditions and student involvement. The results of the observation showed that the learning environment in this school was quite conducive, with facilities that supported the learning process. In implementing the local cultural approach, teachers introduced flat geometry through the Sikambang Art element, which succeeded in increasing students' interest and understanding of the material. Interviews with teachers revealed that this approach was effective in deepening students' understanding, although there were several challenges such as limited cultural-based teaching materials. Overall, this study shows that a local cultural-based approach can enrich the mathematics learning process and foster students' appreciation of their own culture, thereby increasing the effectiveness of learning in the classroom.